2015
DOI: 10.1002/path.4563
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental control of stem cell fate in intestinal homeostasis and disease

Abstract: The conventional model of intestinal epithelial architecture describes a unidirectional tissue organizational hierarchy with stem cells situated at the crypt base and daughter cells proliferating and terminally differentiating as they progress along the vertical (crypt–luminal) axis. In this model, the fate of a cell that has left the niche is determined and its lifespan limited. Evidence is accumulating to suggest that stem cell control and daughter cell fate determination is not solely an intrinsic, cell aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 61 publications
0
47
0
Order By: Relevance
“…Despite an intense focus on ISC dynamics during the past 10 years,7, 8, 11, 16 an understanding of how distinct stem cell populations are differentially and coordinately regulated is not clear. Although there are studies describing stem cells as harboring intrinsic regulatory programs, 17 it is suggested that the dominant influence derives from the niche 18, 19…”
mentioning
confidence: 99%
“…Despite an intense focus on ISC dynamics during the past 10 years,7, 8, 11, 16 an understanding of how distinct stem cell populations are differentially and coordinately regulated is not clear. Although there are studies describing stem cells as harboring intrinsic regulatory programs, 17 it is suggested that the dominant influence derives from the niche 18, 19…”
mentioning
confidence: 99%
“…Thus, colonic biopsies represent intestinal-specific transcriptional patterns consisting of signals originating from stromal and epithelial cells (7,12,24). To dissect the role of epithelial and stromal genes in intestinal homeostasis, we recently demonstrated in an NSAID clinical trial that the expression of genes involved in cell signaling, cellular movement, and cancer differed significantly [P Ͻ 0.01, false discovery rate (FDR) Ͻ0.001] in the epithelium and stroma (53).…”
mentioning
confidence: 99%
“…The ISC niche is a major regulator of ISC homeostasis and comprises several cell types that are found in the crypt region including: Paneth (deep crypt cells in colon), stromal/myofibroblast and immune cells [26, 27] (Figure 2). Paneth cells in the small intestine are capable of secreting signals for ISC health (Wnt3, EGF, Notch receptor ligands).…”
Section: Isc Niche Cellsmentioning
confidence: 99%
“…The lamina propria also contains immune cells that contribute to the regulation of ISCs. Most notably, immune cells secrete cytokines such as IL-6 and IL-17 which can stimulate ISC proliferation [26]. Recently it has been shown that inhibition of IL-6 signaling (via a neutralizing antibody) can prevent inflammation-induced ISC proliferation [36].…”
Section: Isc Niche Cellsmentioning
confidence: 99%